POWER, ORIENTATION, AND STRATEGY OF POSITIVE POLITENESS USED BY CHILDREN AT THE AGE OF ELEMENTARY SCHOOL WITH JAVANESE CULTURAL BACKGROUND - Prayitno, Harun Joko; Ngalim, Abdul; Sutopo, Anam; Rohmadi, Muhammad; Yuniawan, Tommi (Humanus, 2018)
Politeness strategies in primary school is the foundation of character building. This study aims to identify the power and orientation of positive politeness strategies used by the children at the age of elementary school as the character of Indonesian. This study applies qualitative research with single-case study strategy. The data source consists of all elementary school teachers and students in Surakarta and Yogyakarta. The data were collected by using active observation and focus group discussion.  The data are in the forms of  teaching materials. The data were analyzed using heuristic model proposed by Grice & Leech by applying the principles of reconciliation, cultural and social harmony. The result shows that the elementary school teachers and students having the Javanese cultural background indicated by (a) building the nature of psychological as the core of positive politeness and nation character by improving the empathy feeling, looking for the agreement, giving respect,  appreciating the achievement, and giving the profit to another; (b) prioritizing the duty instead of the rights; (c) creating the wise of directive act strategyby positioning the listener ; (d) respecting others to show the suavity and politeness. Therefore, the Javanese society in line with directive politeness action always put the environment society to keep its social-societal relationship. Keywords: directive politeness, harmony principle, javanese cultural,positive politeness, socio-societal AbstrakStrategi kesantunan di sekolah dasar adalah fondasi pembentukan karakter. Penelitian ini bertujuan untuk mengidentifikasi kekuatan dan orientasi strategi kesantunan positif anak-anak di usia sekolah dasar sebagai karakter bangsa Indonesia. Penelitian ini merupakan penelitian kualitatif dengan jenis studi kasus tunggal. Sumber data terdiri dari semua guru sekolah dasar dan anak-anak usia SD di Surakarta dan Yogyakarta. Data dikumpulkan dengan menggunakan observasi aktif dan diskusi kelompok fokus. Data tersebut berupa bahan ajar. Data dianalisis menggunakan model heuristik yang diajukan oleh Grice & Leech dengan menerapkan prinsip rekonsiliasi, budaya dan keharmonisan sosial. Hasilnya menunjukkan bahwa guru sekolah dasar dan anak-anak usia SD yang memiliki latar belakang budaya Jawa ditunjukkan dengan (a) membangun sifat psikologis sebagai inti dari kesantunan positif dan karakter bangsa dengan meningkatkan perasaan empati, mencari kesepakatan, memberikan rasa hormat, menghargai pencapaian, dan memberikan keuntungan kepada yang lain; (b) memprioritaskan tugas dan bukan hak; (c) menciptakan strategi tindakan yang efektif dengan memposisikan pendengar; (D) menghormati orang lain untuk menunjukkan kesantunan. Oleh karena itu, masyarakat Jawa sejalan dengan tindakan kesopanan direktif selalu menempatkan masyarakat lingkungan untuk menjaga hubungan sosial-kemasyarakatannya.Kata Kunci: kesantunan direktif, prinsip harmoni, budaya jawa, kesantunan positif, sosio-sosietal.